Effect of tiotropium bromide combined with salmeterol fluticasone inhalation on airway function and airway inflammation in patients with moderate-severe stable COPD - Min Xiang (Journal of Hainan Medical University, 2016)
Objective: To analyze the effect of tiotropium bromide combined with salmeterol fluticasone inhalation on airway function and airway inflammation in patients with moderate-severe stable COPD. Methods: A total of 118 patients with moderate-severe stable COPD were randomly divided into observation group and control group (n=59), control group accepted routine treatment, observation group received tiotropium bromide combined with salmeterol fluticasone inhalation treatment, and then differences in the levels of small airway function and airway wall parameters, the content of inflammatory factors and chemokines in serum and so on were compared between two groups of patients after 2 weeks of treatment. Results: After 2 weeks of treatment, small airway function parameters FEF25, FEF25-75 and FEF75 levels of observation group were significantly higher than those of control group, airway wall parameters WT, WA and T/D levels were significantly lower than those of control group, and AI level was significantly higher than that of control group; MIP-1α, PCT, NF-κ B, IL-6, CRP, Eotaxin, CCL18, Lymphotactin, sFKN and MCP-1 content in serum of observation group were significantly lower than those of control group while sTNFR content was significantly higher than that of control group. Conclusions: Tiotropium bromide combined with salmeterol fluticasone inhalation therapy can optimize the overall condition in patients with moderatesevere stable COPD, which is specifically reflected on the control of the airway function and the degree of inflammation.